Chinese standards from the ground up - Driessen, M; Zhu, R (SAGE Publications, 2024)
China’s transformation from a standards-taker to a standards-maker has sent a shock wave through the global economy. While Chinese standardization is conventionally perceived and analysed as a top–down process, led by the central government and the Standardization Administration of China, this article demonstrates the merits of studying standards from the ground up. Sustained engagement with those who make, adopt, reject, and recalibrate standards reveals, first, the human face of standardization. Standards depend on people to be their advocates. The effectiveness of their implementation and the scope of their acceptance rely on practitioners who imbue standards with value and promote them within and across national borders. Furthermore, a bottom–up approach sheds light on the hierarchical nature of standards, the processes of inclusion and exclusion, and the dynamics of elevation and marginalization that hierarchies generate. Finally, it prompts us to look beyond de jure standards. As a producer of cheap commodities for developing countries, China has long been a maker of informal, or de facto, standards that grow out of repeat transactions and mutual agreements among actors along these value chains. Only by considering the human, hierarchical, and informal dimensions of standardization can we fully understand China’s rise as a global standards power.